Effects of cutter geometry and cutting parameters on machining Al/SiC Metal Matrix Composites (MMC) - Raja Abdullah, Raja Izamshah; Kasim, Mohd Shahir; Rosman, Muhammad Rafiq; Lamat, Arshad; Salleh, Mohd Shukor; Liew, Pay Jun; Abdul Aziz, Mohd Sanusi; Abdullah, R.S.A. (Penerbit UniMAP, 2021)
Al/SiC Metal Matrix Composite (MMC) have now become one of the prominent materials in composite materials especially in automotive industry. It has gained tremendous demand due to their tailored properties such as lightweight, high strength and wear resistant. However, these materials are classified as poor machinability material due to the presence of the hard-abrasive reinforcement particles within the matrix. Moreover, the lack of commercialization of a specific cutting tool for machining MMC materials is the source of several inherent problems such as rough machined surface and high cutting temperature. Furthermore, most of the researches on machining MMC are merely focus only on the effect of cutting parameters. Addressing to this matter, the development of new cutter design specifically for machining MMC are necessitate. Therefore, the aim of this paper is to study the combined effect between cutter geometrical features (helix angles, rake angles, clearance angles, number of flutes) and cutting parameter (cutting speed, feed rate and depth of cut) towards the machining performances namely surface roughness, cutting force and material removal rate. From the conducted experimental work, it was found that all of the considered factors has significant effect on the machining performances. As a conclusion, the obtained relationship between the responses with the cutter geometrical features and machining parameters can be used for the development of new cutter design specifically for machining Al/SiC MMC material.